Why Do Political Action Committees Give Money to Candidates? Campaign Contributions, Policy Choices, and Election Outcomes - Christopher Magee (Levy Economics Institute of Bard College, 1999)
This paper examines political action committees' motivations for giving campaign contributions to candidates for political office. First, the paper estimates the effect of campaign contributions received by candidates on the outcomes of the 1996 elections to the U.S. House of Representatives. Next, the paper uses a Congressional Quarterly survey of candidates' policy positions to determine the impact of contributions on the policy stances adopted by the candidates. The empirical results suggest that political action committees donate campaign funds to challengers in order to affect the outcome of the election. Campaign contributions received by challengers have a large impact on the election outcome but do not affect the challengers' policy stances on any of the five issues examined in this paper. Campaign contributions to incumbents do not raise their chances of election, however, and affect their policy decisions on only one issue. Some evidence is presented that PAC contributions to incumbents may be given primarily in order to secure unobservable services for the political action committees
Keywords: 330